FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN BERAT BADAN LAHIR RENDAH (BBLR) DI KABUPATEN KUDUS (Studi di Wilayah Kerja Puskesmas Undaan Kecamatan Undaan Kabupaten Kudus Tahun 2015) - Chintya Putri Haryanto; Siti Fatimah Pradigdo; M. Zen Rahfiluddin (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The percentage of infants with low birth weight in Puskesmas Undaan is the highest in the district of Kudus in 2014, that is 5.87% of 753 births, almost the same as the month of January to October 2015 amounted to 5,89% of the 594 births. The nutritional status of pregnant women such as chronic energy deficiency (CED) and anemia, may affect the nutritional status of the fetus and cause babies have low birth weight (LBW). Other factors such as parity, spacing pregnancies, maternal age and maternal height also at risk for LBW. The aim of this study was to analyze factors associated with LBW. This type of research is quantitative approach using a case control study. The population is all women who gave birth from 2014 to October 2015 in Puskesmas Undaan (1047 mothers). The research sample number of 88 samples consisting of 44 cases samples and 44 control samples. Secondary data were obtained from maternal cohort and infant cohort and cases of data the incidence of low birth weight and the risk of pregnant women. Analysis of data using statistical test Chi-Square with a 95% confidence level. The analysis shows, there is no relationship between KEK with LBW (p = 0.127; 95% CI = 0.787 to 6.242; OR = 2.217). There is no relationship between anemia with LBW (p = 0.107; 95% CI = 0.749 to 12.320; OR = 3.037). There is a relationship between parity with LBW (p = 0.020; 95% CI = 1.180 to 11.230; OR = 3.640). There is no relationship between pregnancy spacing with LBW (p = 0.534; 95% CI = 0.430 to 5.062; OR = 1.476). There is a relationship between age of pregnant women with LBW (p = 0.037; 95% CI = 1.044 to 6.944; OR = 2.692). There is no relationship between the height of mothers with LBW (p = 0.097; 95% CI = 0.820 to 8.247; OR = 2.600). In conclusion, there is a relationship between parity and age of pregnant women with LBW in the Puskesmas Undaan Kudus.